Comparative study on the behaviour of granular pile anchors and helical pile anchors in expansive soils subjected to swelling. Issue 1 (2nd January 2020) - Muthukumar, M.; Shukla, Sanjay Kumar
Abstract: Several foundation techniques, such as belled piers, under-reamed piles, helical piles are adopted in expansive soils to avoid the problem posed by its swelling nature. In recent years, the granular pile anchor (GPA) technique has been in practice for resisting the uplift of foundation caused by expansive clay beds. Model and prototype studies on GPA revealed that swelling of expansive clay beds can be effectively controlled by the GPA technique. This paper presents a comparative study on the behaviour of GPA and helical pile anchors (HPAs) in expansive soil subjected to swelling. The data presented in this paper pertain to model tests of clay beds reinforced with varying number of GPAs ( N = 0, 1, 2 and 3). Similarly, the model tests were conducted on clay bed reinforced with varying number of HPAs ( N = 0, 1, 2 and 3). Tests were also conducted by varying the number of helix. Test results shows that the heave (mm) decreases with an increase in the number of GPAs. Similarly, the heave decreases with an increase in the number of HPA. Further, heave (mm) also decreased with increase in the number of helix. The resultant heave reduction is found to be more in case of expansive soil reinforced with GPA when compared to expansive soil reinforced with helical pile.